The Principles of Multimedia Journalism : Packaging Digital News - Koci Hernandez, Richard; Rue, Jeremy (London Routledge & Kegan Paul, 2015)
In this much-needed examination of the principles of multimedia journalism, experienced journalists Richard Koci Hernandez and Jeremy Rue systemize and categorize the characteristics of the new, often experimental story forms that appear on today's digital news platforms. By identifying a classification of digital news packages, and introducing a new vocabulary for how content is packaged and presented, the authors give students and professionals alike a way to talk about and understand the importance of story design in an era of convergence storytelling. Online, all forms of media are on the
Keywords: Periodismo; Periodismo electrónico